Farmers' Almanac and Traditional Wisdom: Rice Cultivation in the Northern Region of Peninsular Malaysia - Rahimah Abdul Hamid, (Kajian Malaysia, 2015)
Paddy is an important plant as it is the daily staple for large segments of the global population. As such, in some cultures it is revered as a sacred object. To ensure abundant crops, farmers learn from nature thereby creating new knowledge on paddy cultivation. Ancient Malay farmers were sensitive to natural phenomena, observing and taking note of the effects of certain repeated phenomena. From this, they developed methods of segmenting the cycle of rice cultivation (farmer's almanac) and invaluable tips on paddy planting from traditional knowledge. They held steadfast to these practices in the hope of obtaining abundant yield on their crops. This essay shows the extent to which rice farmers still observe traditional knowledge in planting paddy. Nevertheless, modernisation and technological advancement has gradually eroded such practices while those that contravene the Islamic faith have been gradually phased out.